Reducing Manufacturing Defects Using Six Sigma DMAIC: A Case Study in MSG Production - Nur Ramadhan, Andi Naufal; Waluyowati, Nur Prima (Jurnal Kewirausahaan dan Inovasi, 2025)
Purpose – This study aims to analyze product defects in the MSG production process at PT Ajinomoto Tbk Mojokerto and identify appropriate improvement strategies to enhance production quality, efficiency, and consistency. Design/Methodology/Approach – This study applies the DMAIC Six Sigma methodology, consisting of Define, Measure, Analyze, Improve, and Control stages. Defect identification was conducted using the Critical to Quality (CTQ) tree, while defect capability was measured using Pareto Chart analysis and Defect per Million Opportunity (DPMO). The causes of defects were analyzed using Pareto Charts and Fishbone diagrams, followed by Failure Mode Effect Analysis (FMEA) to determine the priority causes requiring improvement actions. Findings – The results identify three main types of MSG production defects: hopper jamming, broken MSG packaging, and product spillage. The FMEA analysis reveals that broken packaging and product spillage are primarily caused by inadequate monitoring and insufficient routine maintenance. The proposed improvement strategies include revising standard operating procedures (SOPs), increasing machinery maintenance frequency, and implementing continuous improvement activities to ensure better production process control and defect reduction. Originality/Value This research is original in integrating DMAIC Six Sigma with FMEA to systematically identify root causes of defects in the MSG production process. The findings provide practical value by offering structured improvement alternatives to reduce defects through better monitoring, maintenance, and standard operating procedures.